Fossil woods from the Cross Valley Formation (Paleocene of Western Antarctica): Araucariaceae-dominated forests - Pujana, Roberto Roman; Marenssi, Sergio Alfredo; Santillana, Sergio N. (Review of Palaeobotany and Palynology)
Fossil woods from Paleocene sediments of the Cross Valley Formation (Seymour Island, Antarctic Peninsula) are anatomically studied in detail. We collected 64 samples represented almost exclusively by conifers (95%). Only three samples of not determinable angiosperm fossil wood were found. Preservation of the samples is often poor and 52% of the samples were assigned to a fossil-species. The assemblage is dominated by Agathoxylon (Araucariaceae), particularly Agathoxylon antarcticus. Araucariaceae species are joined by Protophyllocladoxylon, Phyllocladoxylon and Cupressinoxylon. Forests dominated by Araucariaceae are unusual during the Cenozoic. The high dominance of Araucariaceae woods may be a reflection of soil conditions, weather and terrain elevation. Our study supports previous hypothesis that identified differences between the paleofloras in each side of the Antarctic Peninsula during the Paleocene. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Marenssi, Sergio Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Santillana, Sergio N. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina